On the composition dependence of the microscopic structure, thermodynamic, dynamic and dielectric properties of water-dimethyl formamide model mixtures. Molecular dynamics simulation results - Dominguez, H.; Pizio, O. (Condensed Matter Physics, 2017)
Isothermal-isobaric molecular dynamics simulations have been performed to examine an ample set of properties of the model water-N,N-dimethylformamide (DMF) mixture as a function of composition. The SPC-E and
TIP4P-Ew water models together with two united atom models for DMF [Chalaris M., Samios J., J. Chem. Phys.,
2000, 112, 8581; Cordeiro J., Int. J. Quantum Chem., 1997, 65, 709] were used. Our principal analyses concern
the behaviour of structural properties in terms of radial distribution functions, and the number of hydrogen
bonds between molecules of different species as well as thermodynamic properties. Namely, we explore the
density, excess mixing molar volume and enthalpy, the heat capacity and excess mixing heat capacity. Finally,
the self-diffusion coefficients of species and the dielectric constant of the system are discussed. In addition,
surface tension of water-DMF mixtures has been calculated and analyzed. Здiйснено симуляцiї методом молекулярної динамiки в iзотермiчно-iзобаричному ансамблi з метою вивчення широкого набору властивостей моделi сумiшi вода-N,N-диметилформамiд (DMF) як функцiй концентрацiї. Використано моделi води SPC-E i TIP4P-Ew разом з двома об’єднаними атомними моделями для
DMF [Chalaris M., Samios J., J. Chem. Phys., 2000, 112, 8581; Cordeiro J., Int. J. Quantum Chem., 1997, 65, 709].
Наш основний аналiз стосується поведiнки структурних властивостей в термiнах радiальних функцiй розподiлу i числа водневих зв’язкiв мiж молекулами рiзних сортiв, а також термодинамiчних властивостей.
Зокрема, ми дослiджуємо густину, надлишковi молярний об’єм та ентальпiю змiшування, питому теплоємнiсть i надлишкову питому теплоємнiсть змiшування. Накiнець, обговорюються коефiцiєнти самодифузiї сортiв i дiелектрична стала системи. Крiм того, обчислюється та аналiзується поверхневий натяг
сумiшей вода-DMF.